Effect of Bentonite on Growth and Yield of Wheat in Arid Zone - Misra, D.K.; Bhattacharya, B B (Journal of Soil and Water Conservation, 2022)
The maintenance of proper soil tilth is the main objective of any soil management practice. Purely sandy or purely clayey structures are not desirable. When failures occur in normal growth of plants even after adequate application of fertiliser, they can be attributed to unfavour- able structural condition of soil which affects air water regime of soil and locking up of otherwise readily avail- able nutrients.  Structurcless sandy soils of Western Rajasthan are mainly subject to wind erosion. The addi- tion of organic matter and the adoption of suitable tillage operations are the common methods of obtain- ing proper soil structure. Supply of organic matter being limited to the farmers, suitable substitutes which may help in binding the loose structureless soils have to be investi- gates. Recently beneficial effects of synthetic substances technically known as soil conditioners, that improve soil structure have been reported. Bentonite is one of these soil conditioners which improves the moisture retention capacity and enhances colloidal properties of the soil. The calcium content of soils of arid regions is generally high due to low rainfall and little leaching and thus the lining of soil by the acti- vatcd Bentonite (a sodium Montmo- rillonite claly complex) will release absorbed ions from its colloidal sur- face and take up the calcium. The released ions taken by plants act as plant nutrient. The collidal nature of this chemical also helps the reten- tion of moisture along with the salts necessary for plant growth, which otherwise may get wasted into the subsoil with percolating water (Spence, 1953). In addition to pre- vention of washing out of nutritive substances, this colloidal chemical when present in soil forms fields of various concentrations of electrolytes so that the assembling root base may select the part of the solution that best satisfies it.